The Effect of Leadership Supervision and Employee Commitment on Employee Performance at the Constitutional Court and Corrections Bureau - Veranda Taufica (Jurnal Syntax Admiration, 2023)
The importance of the role of human resources or employees in achieving organizational goals is explained through efforts to improve employee capacity and performance. Employee performance is measured through the achievement of assigned tasks and responsibilities, and to achieve organizational goals, there needs to be organizational supervision and commitment. The purpose of this study is to determine and analyze the effect of leadership supervision on employee performance at the Constitutional Trial and Corrections Bureau at the General Secretariat of the People's Consultative Assembly of the Republic of Indonesia. The results showed that leadership supervision of employee performance at the Constitutional Court and Corrections Bureau, General Secretariat of the People's Consultative Assembly of the Republic of Indonesia, was found to have a significant influence, as indicated by a high correlation level of 0.674. Likewise, employee commitment to the performance of their duties in the same Bureau shows a strong impact on performance, with a correlation coefficient of 0.698. Furthermore, when leadership supervision and employee commitment are considered together, both are proven to have a strong influence on employee performance at the Constitutional Court and Corrections Bureau, General Secretariat of the People's Consultative Assembly of the Republic of Indonesia, with a correlation coefficient reaching 0.746.